Self-defending networks : the next generation of network security - De Capite, Duane (Cisco Press networking technology series., 2006)
Protect your network with self-regulating network security solutions that combat both internal and external threats. Provides an overview of the security components used to design proactive network security Helps network security professionals understand what the latest tools and techniques can do and how they interact Presents detailed information on how to use integrated management to increase security Includes a design guide with step-by-step implementation instructions Self-Defending Networks: The Next Generation of Network Security helps networking professionals understand how to deploy an end-to-end, integrated network security solution. It presents a clear view of the various components that can be used throughout the network to not only monitor traffic but to allow the network itself to become more proactive in preventing and mitigating network attacks. This security primer provides unique insight into the entire range of Cisco security solutions, showing what each element is capable of doing and how all of the pieces work together to form an end-to-end Self-Defending Network. While other books tend to focus on individual security components, providing in-depth configuration guidelines for various devices and technologies, Self-Defending Networks instead presents a high-level overview of the entire range of technologies and techniques that comprise the latest thinking in proactive network security defenses. This book arms network security professionals with the latest information on the comprehensive suite of Cisco security tools and techniques. Network Admission Control, Network Infection Containment, Dynamic Attack Mitigation, DDoS Mitigation, Host Intrusion Prevention, and Integrated Security Management are all covered, providing the most complete overview of various security systems. It focuses on leveraging integrated management, rather than including a device-by-device manual to implement self-defending networks.